Energy Security and Scenario Analysis of Province No. 1 of Federal Republic Nepal - Dulal, Sujan; Shakya, Shree Raj (Journal of Advanced College of Engineering and Management, 2018)
This paper presents the current energy security status of the province No.1 of Nepal using numerous indicators. In addition to that, with the development of six economic growth scenarios i.e. Business As Usual (BAU), Low growth (LOW), High growth (HIG), Accelerated growth (ACC), Normal growth (NOR) and Intervention scenario (INT), the future energy mix and energy security indicators for the year 2040 are also calculated. The paper also gives an overview of the variation/progress of the different indicators during the considered period of study. The study shows that the, energy intensity in the intervention scenario is brought down to 4.44 GJ/1000 compared to that of 15 GJ/1000. Also, the electricity consumption per capita is increased to 574 kWh from 116 in the base year. However, these values are only achieved if the provincial government helps implementing central government’s plan of promoting the electrical systems instead of traditional fuel woods and fossil fuels system.